(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study has been carried out on 48 suckled and weaned rabbits; their age ranged between 0- 30 days suckled and weaned neonates. Body0 weight, crown rump length and forelimb length were recorded. The shape and position of the stomach were observed and its weight, volume, and length of lesser and greater curvature were determined. Also the weight, volume and length of the small and large intestine were recorded. The result showed that the measurements increased with the advancing age and decreased under weaning effect. No change in the shape and position of the stomach was observed in all age groups.